Analysis of the Reliability of the Dissected Frame of Heavy Equipment - 张浩然 颜永年 张人佶 林峰 (Tsinghua science and technology, 2010)
The current research analyzes the reliability of a dissected frame of heavy equipment in terms of stress distribution,integrality,and fatigue.Through the use of the finite element analysis method,the results demonstrated that the stress field and deformation of the dissected frame were identical to those of the integral frame.Under the working condition,slight slides existed along the dissecting planes between arch beams and columns.On the other dissecting positions,there were no slides during either the working state or the pre-stressed state.The wires and frames both appeared to have limitless fatigue lives.Fatigue of the dissected frame was the same as that of the integral frame.This experiment illustrates that dissected frames can meet the requirements of integrality much better than integral frames.At the same time,local slides or detachments along dissecting planes would not expand during long-term service.